The assessment of range of motion in selected joints in competitive swimmers - Radlinska, N.; Berwecki, A. (Journal of Kinesiology and Exercise Sciences, 2015)
Background. Differences in range of motion between groups of athletes specialising in various disciplines result from the specificity of these disciplines. Competitive swimmers spend many hourstraining, which affects motor characteristics, including flexibility. Objective. To assess the difference in mobility of the joints: upper limb girdle, knee joint and ankle joint between groups of competitive swimmers and people who have never trained swimming or any other disciplines and, also, to determine whether there are any differences in range of motion in these joints between groups of swimmers specialising in various strokes. Material and methods. 63 individuals aged 17 to 23 participated in the study. The subject group included 32 competitive swimmers (13 women), with at least 5 years of experience in competitive swimming and minimum 10 training units per week. The control group included 31 individuals (14 women) who were not engaged in any sports discipline (did not participate in more than 3 training units per week). Range of motion in the upper limb girdle was assessed using the Bloomfield test. Extension in the knee joint, dorsiflexion and plantar flexion in the ankle were measured using a goniometer. Inversion and eversion of the foot were measured using an instrument designed by authors. Results. Greater mobility in the upper limb girdle and extension in the knee joint were observed in group of competitive swimmers compared to the control group. Measurement of ankle movement showed that female swimmers had greater dorsiflexion and male swimmers had greater plantar flexion than the controls. Inversion was slightly larger and eversion was smaller in the swimmer group. Conclusions. Competitive swimmers had greater range of motion in the upper limb girdle and the ankle than the control group. Swimmers are also more likely to have hyperextension in the knee joint. Differences in range of motion between groups of swimmers specialising in various strokes were not noticed.